Prokaryotic expression of full coat protein gene of Tomato spotted wilt virus and development of Dot-blot ELISA method for this virus detection - YU Cui; DENG Feng-lin; YANG Cui-yun; WU Jian-xiang (浙江大学学报. 农业与生命科学版, 2008)
The full coat protein gene of Tomato spotted wilt virus (TSWV) was subcloned into a prokaryotic expression vector pET-32a. Results of restriction enzyme digestion and DNA sequencing show that the insertion direction and sequence were correct and no frameshift mutation existed. This recombinant prokaryotic expression vector (pET-32a-TSWV-CP) was used to transform E. coli BL21 (DE3). SDS-PAGE analysis confirmed that the recombinant coat protein with the predicted molecular weight of about 48 kDa was successfully expressed in E. coli BL21 (DE3) strain with the induction of IPTG in the form of a fusion protein. The expressive coat protein was confirmed by 6 × His tag monoclonal antibody and TSWV antiserum raised against TSWV FoPaTs1. The purified recombinant coat protein was used to immunize mouse for production of monoclonal antibody. Using culture supernatants of the hybridoma cell lines, a Dot-blot ELISA method was established for reliable and efficient detection of TSWV in plant samples.